(untitled) (Conference Zone, 2022)
In order to increase students’ motivation for learning, their proficiency and interest in a certain communication style, and their predisposition for a particular profession, it is ideal to use interactive didactic games in the teaching and learning process. The classification of all extant game kinds into functional, thematic, constructive, didactic, sports, and military games is in accordance with the general theory of games. In this essay, we’ll concentrate on the approaches utilized in primary education and discuss how crucial it is to teach young children utilizing interactive methods and pedagogical technology. In this paper, we look for and examine data pertaining to the development of educational and cognitive competency in the primary school English language classroom.